A Preoperative Cognitive Screening Test Predicts Increased Length of Stay in a Frail Population: A Retrospective Case–Control Study. (November 2019) - O'Reilly-Shah, Vikas N.; Hemani, Salman; Davari, Paran; Glowka, Lena; Gebhardt, Emily; Hill, Laureen; Lee, Simon; Master, Viraj A.; Rodriguez, Amy D.; García, Paul S.
Abstract : BACKGROUND: Frailty is associated with adverse perioperative outcomes including major morbidity, mortality, and increased length of stay. We sought to elucidate the role that a preoperatively assessed Mini-Cog can play in assessing the risk of adverse perioperative outcomes in a population at high risk of frailty. METHODS: In this retrospective case–control study, patients who were >60 years of age, nonambulatory, or had >5 documented medications were preoperatively assessed for handgrip strength, walking speed, and Mini-Cog score. The Emory University Clinical Data Warehouse was then used to extract this information and other perioperative data elements and outcomes data. RESULTS: Data were available for 1132 patients undergoing a wide variety of surgical procedures. For the subset of 747 patients with data for observed-to-expected length of stay, an abnormal Mini-Cog was associated with an increased odds of observed-to-expected >1 (odds ratio, 1.52; 95% CI, 1.05–2.19; P = .025). There was no association of abnormal Mini-Cog with intensive care unit length of stay >3 days ( P = .182) discharge to home with self-care ( P = .873) or risk of readmission ( P = .104). Decreased baseline hemoglobin was associated with increased risk of 2 of the 4 outcomes studied. CONCLUSIONS: In a high-risk pool of patients, Mini-Cog may not be sensitive enough to detect significant differences for most adverse outcomes. Further work is needed to assess whether cognitive screens with greater resolution are of value in this context and to compare tools for assessing overall frailty status.